Pengaruh Beban Kerja dan Lingkungan Kerja Terhadap Produktivitas Karyawan di PT. Putra Tunggal Mandiritama Samboja-Kutai Kartanegara-Kalimantan Timur - Muhammad Ridwan; Purbawati Purbawati; Diyaa Aaisyah Salmaa Putri Atmaja; Mad Yusup (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2025)
The research was conducted in the construction department which has around 90 employees with a high workload and a less supportive work environment. The problem in this study is how the workload and work environment affect employee productivity, while the purpose of the study is to determine the effect of workload and work environment on employee productivity. The method used in the study is the multiple linear regression analysis method with a sample of 65 employees. Testing was carried out using the F test and t test and calculating the determination factor. From the results of the t test calculation, the calculated t-value for X1 (workload) was obtained in succession of 3,743 and the calculated t-value for X2 (work environment) was 6.187. These values ​​are greater than the value in the t-table of 1,999, which means that the workload affects employee productivity and the work environment affects employee productivity.The result of the F test calculation produces 14,872 > from the value in the F-table (3,143), it can be concluded that Workload (X1) and Work Environment (X2) have an effect on Employee Productivity (Y) at PT. Putra Tunggal Mandiritama. From the determination coefficient test, the Adjusted R Square value is 0.455 or 45.5%, meaning that the work productivity variable is influenced by the workload and work environment variables by 45.5%. Furthermore, the remaining value of 54.5% is caused by other factors.